2023
DOI: 10.3390/jcm12165293
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Current Concepts and Challenges in the Identification and Management of Early-Stage COPD

Abstract: The need to improve health outcomes, as well as disease prognosis, has led clinicians and researchers to propose new ways of identifying COPD in its earliest forms. This initiative is based on the hypothesis that an earlier intervention would have a greater prognostic impact. However, the operational definition of a patient in the initial stages of the disease is complex, and there is still no unanimously accepted definition. GOLD has recently proposed different concepts to identify COPD in its early stages, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Some authors have suggested this as a potential restrictive pattern, emphasizing the need for total lung capacity (TLC) assessment to draw definitive conclusions. Others categorize it as a non-specific spirometric pattern, but the term Preserved Ratio Impaired Spirometry (PRISm) has gained recent popularity [1,[36][37][38].…”
Section: Forced Spirometry: Flow Volume Curvementioning
confidence: 99%
“…Some authors have suggested this as a potential restrictive pattern, emphasizing the need for total lung capacity (TLC) assessment to draw definitive conclusions. Others categorize it as a non-specific spirometric pattern, but the term Preserved Ratio Impaired Spirometry (PRISm) has gained recent popularity [1,[36][37][38].…”
Section: Forced Spirometry: Flow Volume Curvementioning
confidence: 99%
“…In addition, the current literature consistently predicts a substantial increase in the future health burden of COPD [2]. Despite clear criteria for the diagnosis of COPD, produced by the Global Initiative for Chronic Obstructive Lung Disease (GOLD), being available for two decades [3,4], underdiagnosis and overdiagnosis are still common, causing, in turn, under-or overtreatment, and determining a suboptimal disease management [5][6][7][8]. One recent meta-analysis quantified the rate of underdiagnosis in primary healthcare [9], and several studies estimated the rate of overdiagnosis [10].…”
Section: Introductionmentioning
confidence: 99%
“…Accurate measurement of respiratory flow is vital for the clinical decision-making of chronic obstructive pulmonary disease (COPD) [ 1 , 2 , 3 , 4 ]. The pneumotachograph (PNT) is one of the most common respiratory flow measurement elements used for spirometers.…”
Section: Introductionmentioning
confidence: 99%